Designing intersections-designing subjectivity: feminist theory and praxis in a sex discrimination legislation system - Adam, Alison; Furnival, Ariadne Chloe Mary (Universidade Federal de São Carlos, 1995)
This paper looks at the intersections between feminist epistemology, feminist jurisprudence and research on artificial intelligence and the law. It is suggested that feminist theory highlights the role of subjectivity which is ignored in the traditional epistemology of AI systems. This allows AI systems to appear to be "perspectiveless" when they may be tacitly used in a normative role which ignores alternative knowledges. The paper looks at the Cyc system as an example. In developing an expert system to advise on Sex Discrimination law a number of lessons are learned both from the Forms Helper system and more particularly from feminist jurisprudence and from the critique of AI from feminist epistemology.

Este artigo analisa as interseções entre epistemologia feminista, jurisprudência feminista e pesquisas sobre inteligência artificial e direito. Sugere-se que a teoria feminista destaque o papel da subjetividade que é ignorado na epistemologia tradicional dos sistemas de IA. Isso permite que os sistemas de IA pareçam "sem perspectiva" quando podem ser usados tacitamente em um papel normativo que ignora conhecimentos alternativos. O artigo analisa o sistema Cyc como um exemplo. Ao desenvolver um sistema especialista para aconselhar sobre a lei de discriminação sexual, uma série de lições são aprendidas tanto do sistema Forms Helper quanto, mais particularmente, da jurisprudência feminista e da crítica da IA da epistemologia feminista.
Projetando interseções-projetando subjetividade: teoria e práxis feminista em um sistema legislativo de discriminação sexual
Keywords: IA; Inteligência artificial; Feminismo; Epistemologia feminista; Sistemas especialistas; Lei de discriminação sexual; AI; Artificial intelligence; Feminist epistemology; Sex discrimination law; CIENCIAS SOCIAIS APLICADAS::CIENCIA DA INFORMACAO